Project control - Del Pico, Wayne J
The Basics -- Introduction to Project Control -- Pre-Construction Planning -- The Schedule -- The Budget -- Integrating the Schedule and the Budget -- Calculating and Analyzing Progress -- Analyzing and Reporting Variances in Schedule and Cost -- Recognizing Trends and Forecasting Performance -- Productivity -- Acceleration and Schedule Compression -- Resource Management -- Risk Management -- Project Closeout.; Includes index